Policy Implementation, Financial Management, Bureaucratic Innovation, and Community Participation on Regional Development Planning’s Effectiveness - Warman Warman (International Journal Labs, 2022)
Indonesia is a developing country, therefore development programs continue to be encouraged in all fields because it is important for human survival in the world. To analyze the influence Policy Implementation has on the Effectiveness of South Tangerang City Regional Development Planning and that of Financial Management on the Effectiveness of Tangerang City Regional Development Planning South, this type of explanatory research is a strategy that is quite popular in mixed methods research and is often used by researchers who are inclined to quantitative processes and deemed suitable for this study. Regional development is not solely determined by the potential or wealth of abundant natural resources, but is also determined by systematic development planning, measurable, and comprehensive. Good financial management has been proven to be able to increase the effectiveness of regional development planning. The implementation of the financial management system begins with the formulation of the program and the determination of good performance indicators. It will be very useful to apply because it will serve as a benchmark in achieving the program objectives that have been set.